Postpartum haemorrhage management, risks, and maternal outcomes: findings from the World Health Organization Multicountry Survey on Maternal and Newborn Health. (March 2014) - Sheldon, WR; Blum, J; Vogel, JP; Souza, JP; Gülmezoglu, AM; Winikoff, B; ,
Abstract : Objective: To explore the clinical practices, risks, and maternal outcomes associated with postpartum haemorrhage (PPH). Design: Secondary analysis of cross‐sectional data. Setting: A total of 352 health facilities in 28 countries. Sample: A total of 274 985 women giving birth between 1 May 2010 and 31 December 2011. Methods: We used multivariate logistic regression to examine factors associated with PPH among all births, and the Pearson chi‐square test to examine correlates of severe maternal outcomes (SMOs) among women with PPH. All analyses adjust for facility‐ and country‐level clustering. Main outcome measures: PPH, SMOs, and clinical practices for the management of PPH. Results: Of all the women included in the analysis, 95.3% received uterotonic prophylaxis and the reported rate of PPH was 1.2%. Factors significantly associated with PPH diagnosis included age, parity, gestational age, induction of labour, caesarean section, and geographic region. Among those with PPH, 92.7% received uterotonics for treatment, and 17.2% had an SMO. There were significant differences in the incidence of SMOs by age, parity, gestational age, anaemia, education, receipt of uterotonics for prophylaxis or treatment, referral from another facility, and Human Development Index (HDI) group. The rates of death were highest in countries with low or medium HDIs. Conclusions: Among women with PPH, disparities in the incidence of severe maternal outcomes persist, even among facilities that report capacity to provide all essential emergency obstetric interventions. This highlights the need for better information about the role of institutional capacity, including quality of care, in PPH‐related morbidity and mortality.